Motivation for Domestic Tourists to Visit Pemuteran Tourism Village, Buleleng Regency - Rahmasari, Kadek Aliani; Dianasari, Dewa Ayu Made Lily; Sukariyanto, I Gede Made; Liestiandre, Hanugerah Kristiono (PT FORMOSA CENDEKIA GLOBAL, 2024)
Pemuteran Village is famous for its marine tourism, becoming one of the best diving locations in Bali. This study aims to determine the motivation of domestic tourists to visit Pemuteran Tourism Village. This study is descriptive statistics, data collection through surveys, interviews, observations, and documentation. Surveys by 110 respondents, sample collection in the form of accidental sampling. The results of the study of domestic tourist motivation from the variables of novelty seeking and physical motivation averaged 4.13, stress busting and fantasy motivation averaged 4.03 for achievement and social motivation average value of 3.77, family oriented motivation averaged 4.28 and cultural motivation averaged 3.79. The highest variable motivation is family oriented motivation averaged 4.27 and the lowest motivation is Achievement and Social Motivation averaged 3.78. This study produced three clusters of the K-Maen method, namely exploration cluster, escape cluster and countryside vibes cluster.